DescribePSP and ProPSP: German Multicenter Networks for Standardized Prospective Collection of Clinical Data, Imaging Data, and Biomaterials of Patients With Progressive Supranuclear Palsy - Respondek, Gesine; Höglinger, Günter U. (Frontiers in Neurology, 2021)
Background: The German research networks DescribePSP and ProPSP prospectively collect comprehensive clinical data, imaging data and biomaterials of patients with a clinical diagnosis of progressive supranuclear palsy. Progressive supranuclear palsy is a rare, adult-onset, neurodegenerative disease with striking clinical heterogeneity. Since now, prospective natural history data are largely lacking. Clinical research into treatment strategies has been limited due to delay in clinical diagnosis and lack of natural history data on distinct clinical phenotypes. Methods: The DescribePSP network is organized by German Center for Neurodegenerative Diseases. DescribePSP is embedded in a larger network with parallel cohorts of other neurodegenerative diseases and healthy controls. The DescribePSP network is directly linked to other Describe cohorts with other primary diagnoses of the neurodegenerative and vascular disease spectrums and also to an autopsy program for clinico-pathological correlation. The ProPSP network is organized by the German Parkinson and Movement Disorders Society. Both networks follow the same core protocol for patient recruitment and collection of data, imaging and biomaterials. Both networks host a web-based data registry and a central biorepository. Inclusion/exclusion criteria follow the 2017 Movement Disorder Society criteria for the clinical diagnosis of progressive supranuclear palsy. Results: Both networks started recruitment of patients by the end of 2015. As of November 2020, N=354 and N=269 patients were recruited into the DescribePSP and the ProPSP studies, respectively, and N=131 and N=87 patients received at least one follow-up visit. Conclusions: The DescribePSP and ProPSP networks are ideal resources for comprehensive natural history data of PSP, including imaging data and biological samples. In contrast to previous natural history studies, DESCRIBE-PSP and ProPSP include not only patients with Richardson´s syndrome, but also variant PSP phenotypes as well as patients at very early disease stages, before a diagnosis of possible or probable PSP can be made. This will allow for identification and evaluation of early biomarkers for diagnosis, prognosis, and progression.